The bouba/kiki effect is robust across cultures and writing systems. (3rd January 2022) - Ćwiek, Aleksandra; Fuchs, Susanne; Draxler, Christoph; Asu, Eva Liina; Dediu, Dan; Hiovain, Katri; Kawahara, Shigeto; Koutalidis, Sofia; Krifka, Manfred; Lippus, Pärtel; Lupyan, Gary; Oh, Grace E.; et al.
Abstract : The bouba/kiki effect—the association of the nonce word bouba with a round shape and kiki with a spiky shape—is a type of correspondence between speech sounds and visual properties with potentially deep implications for the evolution of spoken language. However, there is debate over the robustness of the effect across cultures and the influence of orthography. We report an online experiment that tested the bouba/kiki effect across speakers of 25 languages representing nine language families and 10 writing systems. Overall, we found strong evidence for the effect across languages, with bouba eliciting more congruent responses than kiki . Participants who spoke languages with Roman scripts were only marginally more likely to show the effect, and analysis of the orthographic shape of the words in different scripts showed that the effect was no stronger for scripts that use rounder forms for bouba and spikier forms for kiki . These results confirm that the bouba/kiki phenomenon is rooted in crossmodal correspondence between aspects of the voice and visual shape, largely independent of orthography. They provide the strongest demonstration to date that the bouba/kiki effect is robust across cultures and writing systems. This article is part of the theme issue 'Voice modulation: from origin and mechanism to social impact (Part II)'.